Safety of modified Stoppa approach for Ganz periacetabular osteotomy: A preliminary cadaveric study - Mehmet Elmadağ; Gökçer Uzer; Fatih Yıldız; Hasan H. Ceylan; Mehmet A. Acar (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this cadaveric study was to investigate the efficacy of the modified Stoppa approach in Ganz periacetabular osteotomy (PAO). Methods: The Ganz PAO was performed on 10 hemipelvises with normal hips, from 5 cadavers using the modified Stoppa approach through the Pfannenstiel incision. All of the osteotomies were performed under fluoroscopic control and direct visualizing the osteotomy site from the same incision. After the osteotomy, the acetabulum was medialized and redirected anterolaterally, and fixed with 2 screws. The neurovascular structures and the joints were examined by dissecting the soft tissues after fixation of the osteotomies. Outcome parameters were center-edge (CE) angle, the distances between the osteotomy and anterior superior iliac spine (ASIS), and between the osteotomy and the sciatic notch, neurovascular and joint penetrations. Results: After the osteotomy, the mean CE angle was improved from 19.8° to 25.2°, mean distance between the osteotomy and ASIS was 3.1 cm, and the mean distance between the osteotomy and the sciatic notch was 10.2 mm. The neurovascular structures and the joints were examined by dissecting the soft tissues after fixation of the osteotomies. No damage to the joint, surrounding arteries, veins or nerves was detected in any of the cadavers. Conclusions: Bilateral dysplastic hips can be treated with a 10 cm, cosmetically more acceptable incision in the same session using this approach. Quadrilateral surface of the acetabulum can be directly seen using this approach and the osteotomy can be safely performed. Keywords: Hip, Periacetabular osteotomy, Ganz osteotomy, Modified Stoppa approach